PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI PADA PT. DIPO INTERNASIONAL PAHALA OTOMOTIF PADANG - Nazarudin Aziz; Muhamad Fadly (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The development of the business world is marked by various fields and services. One of the strategies used in marketing is the marketing strategy. This research aims to analyze the influence of quality product, price, promotion and distribution towards purchasing decisions of Mitsubishi cars at PT. Dipo Internasional Pahala Otomotif Padang. The type of data used in this research is quantitative data sourced from consumers who buy Mitsubishi car products from PT. Pahala Otomotif Padang International Dipo by using the total sampling method with the number of samples used 80 consumers. Data processing use multiple linear regression method. The results of the research that (1) Product has a positive and significant influence to purchasing decisions with a t-count value bigger than t-table 3.841 >1.992 (2) Price has no positive and significant influence on purchasing decisions with a t-count value smaller than t-table -0.514 <1.992 (3) Promotion has no positive and significant influence on purchasing decisions at PT. Dipo Internasional Pahala Otomotif Padang with a t-count value smaller than t-table -0.049>1.992 (4) Distribution has no positive and significant influence on purchasing decisions with t-count smaller than t-table 0.282 <1.992.